Chabacano versus related creoles: (Socio-)linguistic affinities and differences - Holm, John (Sociolinguistic Studies, 2001)
This article compares Zamboangueño (the variety of Chabacano spoken in Zamboanga) with several other creole languages to evaluate the relative importance of superstrate versus substrate influence on their morphosyntax. The presence or absence of parallel morphosyntactic structures are noted in two creole languages that share Zamboangueño´s superstrate but not its substrate (Papiamentu and Palenquero in the Caribbean). Parallels are also noted in Tok Pisin, the restructured English of Papua New Guinea, which shares Zamboangueño´s Austronesian substrate but not its superstrate. The results point to the importance of both superstrate and substrate as a source of creole grammatical features, but suggests that the former may be more influential.